Loss of duodenal folds allows diagnosis of unsuspected coeliac disease. Issue 9 (September 1990) - Corazza, G R; Brocchi, E; Caletti, G; Gasbarrini, G
Abstract : We report three patients with coeliac disease who presented without the classic features of malabsorption and who underwent biopsy and were diagnosed only because of the endoscopic finding of the disappearance of Kerckring's folds in the descending duodenum. This sign constitutes a new and valid aid for the identification of patients with otherwise unsuspected coeliac disease.